Musculoskeletal pain in elderly patient - Michele Cannone (Publiediting, 2010)
Musculoskeletal pain in arthritic and osteoporotic elderly patients is very diffused; if not adequately treated, can constitute cause of permanent invalidity with loss of autonomy, and, in the most serious cases, deaths' cause. The underestimation and the inadequate treatment of pain in the elderly have been object of many studies, whose data are reported in this review.